Incidence of Surgical Site Infections after Thyroid and Parathyroid Surgery: No Role for Antimicrobial Prophylaxis. Issue 6 (June 2018) - Moskalenko, Marina; Asai, Megumi; Beem, Karen; Pezzi, Todd A.; Brophy, Cynthia L.; Noonan, Kristin; Pezzi, Christopher M.
To better define the value of antimicrobial prophylaxis (AMP) and antiseptic skin preparation (ASP) in thyroid and parathyroid surgery, we examined the rate of surgical site infections (SSIs) with and without AMP. Retrospective analysis was performed using the National Surgical Quality Improvement Program database at a single institution. Patients undergoing thyroid or parathyroid surgery with data entered into the National Surgical Quality Improvement Program database at our institution between November 2007 and June 2015 were studied, including patient demographics, wound classification, other risk factors for SSI, and wound outcome. Charts were retrospectively reviewed for AMP, ASP, and use of drains. Of the 534 patients who underwent thyroid (n = 358) or parathyroid (n = 176) surgery, 58 (10.9%) were diabetic, 54 (10.1%) used tobacco, and 14 (2.6%) were on steroids. Most wounds were classified as "clean" (99.6%). Betadine was used for ASP in 96 per cent. AMP was given to 141 patients (26%) using cefazolin, vancomycin, or clindamycin. The remaining 393 patients (74%) received no AMP. Zero infections occurred in the group who did not receive AMP. One (0.7%) superficial, nonpurulent SSI occurred in the group that received AMP which was not statistically significantly different (P = 0.319). The rates of SSI after thyroid and parathyroid surgery are extremely low, around two per 1000 cases, and do not decrease with AMP. Therefore, AMP is not necessary in thyroid and parathyroid surgery and should be avoided to reduce costs, adverse reactions, and antibiotic resistance.